Under the influence of digital media, the sexualization and objectification of idol industry - Huang Huixuan (SHS Web of Conferences)
With the development of media technology, a variety of media platforms appear in the public eye, which also promotes the development of the entertainment industry. It gives fans more channels to follow their favorite idols. This article will explore how the development of the media age affects the degree to which the masses sexualize and objectify idols. The entertainment industry that this article focuses on is the Korean entertainment industry. The results of the study showed that although most fans did not deepen the degree of sexualization and objectification of love beans due to the influence of media development. However, there are still some groups who are influenced by this and sexualize and objectify idols. So there are other factors contributing to the increasing trend of idolization and objectification in the entertainment industry. Among Chinese fan groups, the degree of sexualization and objectification of idols has not been fully affected by the development of the media age.